Life history strategies of Tetranychus ludeni Zacher (Acari: Tetranychidae) with special reference to biological invasion : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Entomology at Massey University, Manawatū, New Zealand - Zhou, Peng (Massey University, 2022)
With the increase of worldwide trade and travel in recent decades, increasingly more arthropod species have become established outside their natural range of distribution, causing substantial ecological and economic impacts in novel habitats. Successful invaders may bear certain life history traits that can overcome various barriers such as mate and food shortage and inbreeding depression. Here, I investigated the life history strategies of a haplodiploid pest, Tetranychus ludeni Zacher (Acari: Tetranychidae), with special reference to its invasion success. It is native to Europe but now cosmopolitan. Virgin females laid larger eggs than mated females, giving rise to larger adults, and sons from virgin females produced more daughters at a higher rate than sons from mated females in their lifetime. Virgin females produced maximum number of sons in their early life to ensure subsequent mother-son mating but later saved resources to prolong longevity for potential future mating. Females maximised their resource allocation to egg production immediately after mating regardless of whether mating delay occurred to secure production of maximum number of both daughters and sons as early as possible. Mated females with mating delay increased proportion of daughters in offspring produced to compensate the loss of production of daughters during their virgin life. Neither mother-son mating nor sibling mating affected female reproductive output and longevity in any of the 11 successive inbred generations and neither sex showed inbreeding avoidance behaviour, suggesting that inbreeding has no negative impact on its invasion success at any points or generations. Mated females did not trade off their survival and lifetime reproductive output with dispersal. Long-distance dispersers invested more in dispersal in their early life while resident mites and short-distance dispersers invested more in reproduction during their early life, which may allow long-distance dispersers to explore the novel environment more effectively without compromising lifetime reproductive fitness. Older females with more mature eggs were more likely to disperse and move longer distances than younger ones with fewer eggs. Females increased dispersal probability and distance with the increase of population density. The synchronization of dispersal and reproduction and the positive density-dependent dispersal strategy may facilitate habitat colonization and invasion speed of T. ludeni. Findings from this study improve our understanding of the invasion mechanisms of T. ludeni and other haplodiploid species, providing knowledge for development of programmes for prediction and management of biological invasions.
Keywords: Tetranychus; Reproduction; Dispersal; Biological invasions; 310913 Invertebrate biology